And then the sky exploded - Poulsen, David A., 1946- (Dundurn, 2016)
Christian Larkin has always admired his great-grandfather Will who was a gifted scientist. But after Will's death, Chris is shocked to learn that he was part of a team that built the atomic bombs that were dropped on Japan during World War II. While on a school trip to Japan, Chris meets eighty-one-year-old Yuko, a survivor who was only eleven-years-old at the time of the attack on Hiroshima, and vows to do something to make up for the devastation caused by his great-grandfather's work.